One-Stop Hybrid Coronary Revascularization Versus Off-Pump Coronary Artery Bypass Grafting in Patients With Multivessel Coronary Artery Disease - Li, Dongjie; Guo, Yulin; Gao, Yingdi; An, Xiangguang; Liu, Yan; Gu, Song; Zhang, Xitao; Zhong, Jiuchang; Gao, Jie; Su, Pixiong (Frontiers in Cardiovascular Medicine, 2021)
Background: Data on one-stop hybrid coronary revascularization (HCR) are limited. This study aimed to compare the early and midterm outcomes of one-stop HCR with off-pump coronary artery bypass graft (OPCAB) in patients with multivessel coronary artery disease. Methods: From April 2018 to May 2021, 752 patients with multivessel coronary artery disease who underwent isolated one-stop HCR or OPCAB were retrospectively included in this analysis. After exclusion and propensity score matching, 151 HCR patients were matched with 151 OPCAB patients. The primary endpoints were midterm major adverse cardiovascular and cerebrovascular events (MACCE) after the procedure. The secondary endpoints were in-hospital complications and outcomes. Results: The preprocedural characteristics were well balanced between the two groups after matching. The HCR group was associated with a lower rate of perioperative transfusion (23.8% vs. 53.0%, P < 0.001) and new-onset AF (5.3% vs. 15.2%, P = 0.004), shorter time of mechanical ventilation (h) [15 (16, 17) vs. 17 (16, 20), P < 0.001] and shorter LOS in the hospital (days) [19 (16, 24) vs. 22 (18, 27), P = 0.001]. Cumulated MACCE rates were similar between the two groups (15.9% vs. 14.0%, P = 0.59) during a median follow-up of 20 months. Conclusions: One-stop HCR is safe and efficacious with less invasiveness and faster postoperative recovery in selected patients with multivessel coronary artery disease. Randomized controlled trials with larger sample sizes and long-term follow-up are warranted to confirm these findings.